2013
DOI: 10.1017/s0016774600001578
|View full text |Cite
|
Sign up to set email alerts
|

Loess in the Vojvodina region (Northern Serbia): an essential link between European and Asian Pleistocene environments

Abstract: Loess deposits in the Vojvodina region, northern Serbia, are among the oldest and most complete loess-paleosol sequences in Europe to date. These thick sequences contain a detailed paleoclimatic record from the late Early Pleistocene. Based on the correlation of detailed magnetic susceptibility (MS) records from Vojvodina with the Chinese loess record and deep-sea isotope stratigraphy we here reconfirm and expand on a stratigraphic model of the Vojvodinian loess-paleosol chronostratigraphic sequence following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
82
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(88 citation statements)
references
References 95 publications
(239 reference statements)
6
82
0
Order By: Relevance
“…Thus the youngest loess layer, V-L1L1, would have accumulated during the upper last glacial period and V-S0 formed during the Holocene. The lithostratigraphical and chronological analysis of the črvenka profile [9] were published in other studies [27,[30][31][32].…”
Section: Paleoecological Results Of the čRvenka Profilementioning
confidence: 99%
See 2 more Smart Citations
“…Thus the youngest loess layer, V-L1L1, would have accumulated during the upper last glacial period and V-S0 formed during the Holocene. The lithostratigraphical and chronological analysis of the črvenka profile [9] were published in other studies [27,[30][31][32].…”
Section: Paleoecological Results Of the čRvenka Profilementioning
confidence: 99%
“…Since the sampling range was 25 cm [27,30,32,85,86], the faunal changes have been examined at a scale of approximately 1250 years (Fig. 5, 6, 7 and 8).…”
Section: Paleoecological Results Of the čRvenka Profilementioning
confidence: 99%
See 1 more Smart Citation
“…While some plateau deposits may contain short hiatuses, luminescence dating and palaeomagnetic profiling have demonstrated that these are generally of short duration (<4 kyrs; Stevens et al, 2007;Zhu et al, 2007) and that on the longer timescales that are relevant to basin-wide, long-term unified stratigraphic models, these are not significant. Many Danubian sequences are formed in plateau-like depositional environments comparable to the Chinese Loess Plateau, where relatively continuous, uniform and well-preserved loess records facilitate relatively straight-forward cross correlations between sites (Marković et al, 2012a). We deliberately target these and avoid using other Danubian non-plateau loess sequences, which are characterised by a greater influence of erosional or slope processes (e.g.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Austrian, Slovakian, Czech and geomorphologically more dynamic slope loess linked with fluvial terrace landscapes and local tectonic basins Hosek et al, 2014;Sprafke et al, 2014) yield more complex and incomplete stratigraphic records than those in Hungary or Croatia (Novothny et al, 2009;Wacha and Frechen, 2011;Wacha et al 2013), or in the semi-arid Serbian, Romanian and Bulgarian loess plateau zone (Buggle et al 2009;Marković et al, 2012a). These environmental differences limit the preservation of primary palaeomagnetic and environmental magnetic records, as well as dictating the post-depositional magnetic overprints.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%